Upaya Meningkatkan Keaktifan Belajar Siswa Pada Mata Pelajaran PPKn Melalui Model Pembelajaran Portofolio Kelas XIB SMA Negeri 8 Pontianak - Aryanti, Jopani Ratna; Sulistyarini; Purnama, Shilmy; Mashudi; Bistari (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2023)
This study aims to increase the learning activity of grade XI B SMA Negeri 8 Pontianak students by using the Portfolio learning model in PPKn subjects. The research method used in this study is classroom action research with a descriptive form. The subject of this study was class XI B SMA Negeri 8 Pontianak which amounted to 30 students. Data collection techniques and instruments are observation sheets and documentation. The study was conducted in two cycles. Each cycle consists of three meetings, and each meeting consists of four stages, namely the planning stage, the implementation and observation stage, and the reflection stage. Based on the results of the study, individual student learning activity increased, in cycle I student learning activity reached an average of 73.85%, and the average student learning activity individually in cycle II was 82.54%. Based on the results of the study, it can be concluded that the application of the Portfolio learning model in PPKn subjects can increase the learning activity of grade XI B SMA Negeri 8 Pontianak students